THE ROLE OF THE LIBRARY IN IMPROVING EDUCATION QUALITY IN SMA NEGERI 3 MEDAN - Asrul Asrul; Rudi Purwana (UIN Sumatera Utara, 2021)
The goal of this research was to determine the role of libraries in improving the quality of education at SMA Negeri 3 Medan as a source of information and learning for students. The research method used in this study is a qualitative research method with a descriptive approach. The study's findings indicate that the library at SMA Negeri 3 Medan serves as a cyber library to support the learning process at SMA Negeri 3 Medan by providing information to improve educational quality.